Pola Komunikasi Kepala Desa dalam Meningkatkan Kinerja Aparatur di Kantor Desa Gunung Jaya Cisaat Kabupaten Sukabumi - Eka Susilawati; Alwy Elnandar Zikri (Jurnalika : Jurnal Ilmu Komunikasi, 2022)
Every individual in the organization is required to always interact with each other, be it communication from top to bottom or vice versa, as well as communication between others. That way, the flow of communication can be effective. In addition, the leadership role is very vital to direct, control, instruct and mobilize every member in the organization, so that the sustainability and goals of the organization can be fully achieved. This kind of communication climate can actually be created in all forms of organization, including government institutions, in this case the village office. Village government as a form of organization certainly cannot be separated from the communication activities carried out by the individuals in it. This study aims to determine organizational communication patterns in improving employee performance at the Gunung Jaya Village Office, organizational communication barriers, and communication strategies in improving employee performance. The research method is descriptive qualitative with data collection techniques of participation observation, observation, and interviews. The results of the research on organizational communication patterns carried out in the Gunung Jaya Village office were carried out formally and informally. Formal communication patterns include downward and upward communication patterns, as well as horizontal. The formal downward communication pattern is carried out once a month, unless there are incidental rules or instructions from the sub-district or district government. There are communication barriers due to overuse of communication tools at the wrong time, delays in conveying information about the implementation of a job or report. Meanwhile, the strategy carried out by the leadership is to improve employee performance by providing direction, input, motivation and encouragement, as well as going directly to the field to provide direct support to employees.